The Relationship between Nutritional Literacy, Body Image, and Pocket Money with Sweet-Sugar Beverages (SSB) Consumption in Adolescents - Sekar Arum Kinasih (Lembaga Pengembangan Kinerja Dosen, 2026)
The consumption pattern of sugar-sweetened beverages (SSBs) among adolescents has shown a worrying increase in recent years. It has been linked to various adverse health outcomes, such as an increased risk of obesity, diabetes-mellitus, and other metabolic disorders. Several factors may influence this consumption behaviour, including nutrition literacy, body image, and the amount of pocket money adolescents receive. This article aims to critically review and analyze scientific findings related to the relationship between nutrition literacy, body image, and pocket money and adolescents' consumption of SSBs. The method used in this article is a literature review of scientific articles obtained through PubMed, Elsevier, ScienceDirect, and Google Scholar, with inclusion criteria including international articles published within the last five years (2020–2025) relevant to the topic and peer-reviewed. The review findings indicate that higher nutrition literacy is associated with healthier dietary behaviours and reduced sugar- sweetened beverage (SSB) consumption. Body image has a significant role in emotional eating, including SSB intake. Additionally, greater pocket money is linked to higher consumption of SSBs. These three factors are interrelated and influence adolescent consumption patterns. Therefore, comprehensive interventions should be designed in cognitive, psychosocial, and economic aspects through sustainable, adolescent-centered nutrition education.